Unpacking EFL Teachers’ TPACK thru the Distance Education - Sofia Imania; Mirjam Anugerahwati; Sintha Tresnadewi (Graduate School of Universitas Negeri Malang, 2022)
Abstract: The growth of distance education provides an accessibility of teaching-and-learning-process involving the use of ICT. Hence, teachers’ competencies regarding the integration of ICT also one of the key success of teaching. Through TPACK, this study aims at investigating EFL teachers’ skills on technology integration and their preferable ICT based learning system amidst distance education. Moreover, this study also intends to analyze whether EFL teachers’ TPACK are significantly different in terms of teaching categories and gender. This survey study implicated 139 in-service EFL teacher in the city of Malang, East Java, Indonesia. The data were collected through questionnaire and analyzed by computing the frequency, ANOVA, and t-test. The finding revealed that the EFL teachers’ TPACK was decent. Furthermore, gender and teaching categories were not regarded as the factors that influenced EFL teachers’ TPACK. Lastly, Google Classroom was perceived as the most preferable ICT based learning system according to the teachers. Regarding the result of analysis, recommendation for teachers and educational stakeholders were also made in this study.Abstrak: Perkembangan Pendidikan Jarak Jauh (PJJ) menawarkan aksesibilitas proses belajar-mengajar yang sangat melibatkan penggunaan TIK. Karenanya, kompetensi guru terhadap integrasi TIK juga diangap sebagai salah satu kunci keberhasilan pembelajaran. Melalui TPACK, penelitian ini bertujuan untuk menginvestigasi ketrampilan guru EFL terkait integrasi teknologi dan sistem pembelajaran berbasis TIK yang guru EFL gunakan saat Pembelajaran Jarak Jauh (PJJ). Selain itu, penelitian ini juga bermaksud untuk menganalisa perbedaan TPACK guru EFL berdasarkan kategori mengajar dan gender. Penelitian survei ini melibatkan 139 guru EFL di Kota Malang, Jawa Timur, Indonesia. Pengumpulan data dilakukan menggunakan kuesioner dan dianalisa dengan menghitung frekuensi jawaban responden, ANOVA, dan t-test. Hasil penlitian menunjukkan bahwa TPACK guru EFL baik. Kemudian, gender dan kategori mengajar bukanlah faktor yang membedakan TPACK guru EFL. Terakhir, Google Classroom merupakan media pembelajaran yang paling disukai oleh guru. Berdasarkan hasil analisa, rekomendasi untuk guru dan beberapa pihak terkait juga dibuat dalam penelitian ini.